PEMANFAATAN HASIL EVALUASI PEMBELAJARAN DALAM PENGEMBANGAN PROGRAM PEMBELAJARAN ANAK USIA DINI - Akhsanti, Munika Sarri (BELIA: Early Childhood Education Papers, 2014)
Evaluasi merupakan salah satu komponen pokok yang harus dipahami guru. Artinya evaluasi dianggap penting dan strategis karena hasil evaluasi berkatian dengan kepentingan semua pihak seperti guru, siswa, orang tua, pemerintah dan masyarakat luas. Disamping itu hasil evaluasi juga digunakan untuk perbaikan program pembelajaran. Tujuan penelitian ini adalah untuk mengetahui pelaksanaan evaluasi pembelajaran di TK Al-Mubaarok, untuk mengetahui pemanfaatan hasil evaluasi pembelajaran dalam pengembangan program pembelajaran di TK Al-Mubaarok, serta mengetahui faktor pendukung dan penghambat pemanfaatan hasil evaluasi pembelajaran dalam pengembangan program pembelajaran di TK Al-Mubaarok. Jenis penelitian yang digunakan adalah deskriptif kualitatif. Informan penelitian adalah guru dan kepala sekolah TK Al-Mubaarok. Metode pengumpulan data yang digunakan yaitu wawancara, observasi dan dokumentasi. Keabsahan data penelitian menggunakan tringulasi sumber. Analisis data yang digunakan yaitu reduksi data, display data dan verifikasi data. Hasil penelitian menunjukkanÂ  bahwa pelaksanaan evaluasi pembelajaran di TK Al-Mubaarok sudah sesuai dengan pedoman yang digunakan oleh TK Al-Mubaarok yaitu model penilaian kelas dan standar penilaian dalam PERMEN 58 Tahun 2009.Â  Pemanfaatan hasil evaluasi pembelajaran dalam pengembangan program pembelajaran dilakukan oleh guru TK Al-Mubaarok yaitu hasil evaluasi dimanfaatkan untuk mendiagnosis kesulitan belajar anak, melakukan bimbingan terhadap anak, memotivasi anak, menetukan tujuan pembelajaran, mengembangkan materi, mengembangkan kegiatan pembelajaran menyenangkan, menentukan metode yang akan digunakan, mengembangkan media, merencanakan evaluasi berikutnya serta pengorganisasian kelas. Faktor pendukungnya adalah kepemimpinan kepala sekolah yang baik, faktor penghambatnya adalah kendala waktu dan semangat guru yang fluktuatif sehingga berakibat pada pemanfaatan hasil evaluasi kurang maksimal.The research problems are include (1)Â  How is the cooperative model type talking stick which is helped multimedia quiz creator to improve the senior high school studentsâ folklore attentive skill. (2) how is the principles of cooperative model type talking stick development which is helped by multimedia quiz creator to improve theÂ  senior high school studentsâ folklore attentive skill. This research uses research and development design (R&D), this research developes model whichÂ  have been exist that is cooperative model type talking stick into cooperative model type talking stick which is helped by multimedia quiz creator. The results of the researches are : (1) the teacher and studentsâ need toward to cooperative model type talking stick which is helped by multimedia quiz creator. (2) cooperative model type talking stick priciples are (a) innovative learning strategy, (b) innovative learning media, (c) assessment. Evaluation is one of the basic components that must be understood teacher. That meaning is an important and strategic evaluation because the results of the evaluation association with the interests of all parties such as teachers, students, parents, government and the wider community. Besides, the results of the evaluation are also used for the improvement of learning programs. The purpose of this research was to determine the evaluation of learning in kindergarten Al-Mubaarok, to examine the use of evaluation results in the development of learning in learning program at kindergarten Al-Mubaarok, and to know the factors supporting and inhibiting the utilization of evaluation results in the development of learning in learning program at kindergarten Al-Mubaarok. This type of research is descriptive qualitative. The informants are teachers and principal of kindergarten Al-Mubaarok. Data collection methods used were interviews, observation and documentation. The validity of research data using tringulasi source. Data analysis used the data reduction, data display and data verification. The results showed that the implementation of the evaluation of learning in kindergarten Al-Mubaarok is in conformity with the guidelines used by the kindergarten Al-Mubaarok the model class and assessment standards in the assessment of Mnistrial Regulation No. 58 of 2009. Using the findings of the evaluation of learning in the development of learning programs conducted by teacher of kindergarten Al Mubaarok the results of the evaluation are used to diagnose a childs learning difficulties, conduct counseling to children, to motivate children, determine the learning objectives, developing materials, develop fun learning activities, determine the method to be used, develop a media plan for subsequent evaluation and organization of classes. Supporting factors is a good school leadership, the inhibiting factor is time constraint and spirit teachers fluctuating resulting in less than the maximum utilization of the evaluation results.